2022
DOI: 10.1007/s10614-022-10325-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Bitcoin Prices using Signal Processing Methods, Bayesian Optimization, and Deep Neural Networks

Abstract: Bitcoin is a volatile financial asset that runs on a decentralized peer-to-peer Blockchain network. Investors need accurate price forecasts to minimize losses and maximize profits. Extreme volatility, speculative nature, and dependence on intrinsic and external factors make Bitcoin price forecast challenging. This research proposes a reliable forecasting framework by reducing the inherent noise in Bitcoin time series and by examining the predictive power of three distinct types of predictors, namely fundamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
0
5
0
3
Order By: Relevance
“…In recent years, many scholars directly studied on prediction of BTC (Adcock and Gradojevic, 2019; Atsalakis et al ., 2019; Pabuccu et al ., 2020; Hau et al ., 2021; Tripathi and Sharma, 2023; Wang and Hausken, 2022). Huang and Gao (2022) used least absolute shrinkage and selection operator (LASSO) approach to predict BTC returns from 2018 to 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, many scholars directly studied on prediction of BTC (Adcock and Gradojevic, 2019; Atsalakis et al ., 2019; Pabuccu et al ., 2020; Hau et al ., 2021; Tripathi and Sharma, 2023; Wang and Hausken, 2022). Huang and Gao (2022) used least absolute shrinkage and selection operator (LASSO) approach to predict BTC returns from 2018 to 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Tripathi and Sharma (2022), DNNs demonstrate superior performance compared with LSTM and CNN-LSTM models when predicting BTC prices using technical indicators as model inputs. In addition, Omar et al (2022) employed a DNN to process denoised inputs, and the proposed model outperformed traditional statistical methods such as ARIMA.…”
Section: Deep Neural Network (Dnns)mentioning
confidence: 99%
“…The findings have indicated that the methodology is put into use to forecast more accurately [4]. However, because of the erratic price swings of bitcoin and the constantly shifting structure of the market, traders as well as investors are exposed to dangers that could result in significant monetary losses, making it challenging for scholars to innovative methods for price prediction that increase accuracy [5].…”
Section: Introductionmentioning
confidence: 99%